Improving Taxpayer Compliance Through Behavioral Approach - Nilam Kesuma; Patmawati Patmawati; Rela Sari; Nur Khamisah (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2023)
This research will be conducted to find out more about taxpayer compliance in terms of a behavioral approach using the Theory of Planned Behavior (TPB) using three indicators, namely attitudes towards behavior, subjective norms, and behavioral control. The data used is primary data obtained directly from individual taxpayers in the KPP Madya Palembang as respondents by using questionnaires distributed to 130 respondents. The sampling technique used is non-probability sampling with purposive sampling method. The results showed that there was a significant influence partially or simultaneously on attitudes, behavior, subjective norms, and behavioral control